Performance Evaluation of Dry Faecal Sludge-Derived Activated Carbon (DFSAC) for Wastewater Pollutant Removal: A Case Study of the Lavender Hill Faecal Treatment Plant - Issahaku Ahmed; Esi Awuah; Helen M. K. Essandoh; Sampson Oduro-Kwarteng; Dennis Ofori-Amanfo; Florence Cobbold (Advances in Materials Science and Engineering)
This study evaluates the applicability of dry faecal sludge activated carbon (DFSAC) as a wastewater pollutant removal technology by employing both laboratory- and large-scale setups. The setups were monitored using effluent from the Mudor wastewater treatment plant in Accra. The DFSAC was produced from primary sludge obtained from a primary treatment to treat approximately 1000 liters of effluent water per hour to meet the needs of backwashing, cleaning, irrigation, and flushing purposes. The laboratory-scale experiment was monitored for a period of two weeks, while the large-scale experiment was monitored for a period of 16 weeks. Physicochemical, microbial, and metal characteristics were analyzed for the polished effluent. The results obtained from the lab scale showed high removal efficiencies of the wastewater pollutants for the first and second weeks of treatments, respectively, as follows: colour (99.47%, 69.06%), turbidity (99.59%, 42.59%), COD (96.58%, 43.49%), BOD (99.26%, 77.42%), TSS (100%, 62.296%), TDS (92.92, 32.90), ammonia (98.41%, 50.83%), and EC (73.60%, 19.94%). The P value obtained indicated a highly significant difference between the influent and effluents of both weeks. The large-scale application of the DFSAC yielded a percentage reduction of 99.36%, 99.37%, 99.52%, 79.63%, 100%, 48.85%, 90.08%, and 46.72% for colour, turbidity, COD, BOD, TSS, TDS, ammonia, and EC, respectively. The DFSAC showed high removal potential for heavy metals and microbial contaminants over the study period. Pollutant removal in wastewater with DFSAC proved a promising intervention by significantly reducing pollutants in wastewater effluent as a tertiary treatment. The removal efficiencies are indications that physisorption and chemisorption play an important role in the adsorption of pollutants onto the DFSAC. The study has shown that faecal sludge can be used as activated carbon for remediation of wastewater pollutants, especially in treatment facilities, which do not meet EPA effluent discharge guidelines while ensuring a close resource utilization loop.